Social Sustainability Reporting and Board Structures in the Healthcare Industry - Adamu Idris Adamu; Irma Tyasari (Indonesian Journal of Sustainability Accounting and Management, 2022)
This paper aims to analyze the structure of the corporate board that triggers social sustainability reporting in the healthcare industry. The sample consists of 60 firm-year observations. Data on corporate governance was collected from the annual reports of the sampled companies and social sustainability data were obtained from MachameRatios. Moreover, financial information was collected from the NSE factbooks. Consistent with the study’s predicted hypotheses, the result reveals that companies with several directors and with one or more female directors as board members are more likely to report social sustainability activities. However, having nonexecutive directors on the board had limited impact on issues relating to sustainability. Our study adds to the existing literature on board structures and sustainability reporting that large and diverse boards are material determinants of social sustainability reporting. The study findings are consistent with various regulatory bodies’ initiatives (for example, the Securities and Exchange Commission of Nigeria) on board structures. The commission mandated all listed firms to have at least five directors. Hence, encouraging companies to have larger and diverse boards composed of mixed genders with greater experience will positively impact sustainability reporting.